PROGRAM RELOKASI PERMUKIMAN BERBASIS MASYARAKAT UNTUK KORBAN BENCANA ALAM LETUSAN GUNUNG MERAPI TAHUN 2010 (Community Based Resettlement Program for the Victims of Natural Disaster of Merapi Volcano Eruption 2010) - Paulus Bawole (Tesa Arsitektur, 2015)
The most active volcanoes in Indonesia, Mount Merapi erupted with devastating in October and November 2010. Besides some infrastructure facilities are damage, about 2,900 houses were destroyed. 350,000 people were evacuated and accommodated in refugee camps. To accommodate the survivors of Merapi Volcano eruption whose houses were destroyed by the heat clouds it necessary to find a strategy for integrated housing development which is environmental friendly and sustainable. The strategy which is choosen to implement relocation program for survivors of Merapi eruption is the Community-Driven Resettlement. Community involvement from the beginning of the planning process until the end shows that the power of community involvement in the development process greatly affect the sense of belonging the residential area. By the strategy of Community-Driven Resettlement the inhabitants can keep, maintain, and develop their settlements very well. The development of sustainable resettlements was planned holistically by considering aspects of disaster mitigation, eco-settlement and community livelihood.